Сучасні альтернативні форми шлюбу - Ляшенко, Наталія Олександрівна (Харківський національний університет внутрішніх справ, 2009)
Alternative forms of marriage are reviewing not only the form but the meaning of relations between spouses. The aim of the article is to describe alternative forms of modern marriages. The article explains the reasons for their appearance and the factors that primarily affect their distribution. Particular attention is given to the cohabiting marriage as the most common type of alternative marriage, explained the functions that it primarily performs, or fails to perform. It was emphasized that the distribution of alternative types of marriage and equating them to the official marriage will lead to the problem of identification of marriage as a social institution, uncertainty in the performance of marital roles, in the scope of the rights and responsibilities of spouses
Modern alternative form of marriage
Keywords: соціальні інститути; сім'я; сезонний шлюб; комунальний шлюб; відкритий шлюб; гостьовий шлюб; раціональний шлюб; гомосексуальні шлюби; цивільний шлюб; функції шлюбу